Dismantlings : words against machines in the American long seventies - Tierney, Matt, 1976- (Cornell University Press, 2019)
"A counter-lexicon for theorizing technology in our digital present, Dismantlings recovers critical keywords from radical literary and activist writing of the Long Seventies in the United States"--